Using the Internet to strengthen curriculum - Lewin, Larry, 1949- (Association for Supervision and Curriculum Development, 2001)
Today's students literally grew up with the Internet. For too many students, though, the glowing computer screen in front of them is just another game platform, shopping mall, or telephone line. But teachers who can help students use the Internet as a learning tool will improve their instruction and their students' learning. Using the Internet to Strengthen Curriculum is not a technical book; rather, it is a book about teaching. Its focus is on helping teachers learn how to bring the Internet's.